2001
DOI: 10.1111/j.1834-7819.2001.tb00273.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of the dental treatment needs of children with disabilities in Melbourne, Australia

Abstract: A selected population of children with disabilities in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
58
3
9

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 12 publications
14
58
3
9
Order By: Relevance
“…Meanwhile, cerebral palsy subjects who are often mentally retarded have high prevalence of class II [15,41] attributed to early eruption of primary teeth and abnormal tongue and head posture [15,[42][43][44]. Furthermore, lip incompetence and failure of the maxillary orbicularis muscle is another cause of excessive overjet in cerebral palsy patients [45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, cerebral palsy subjects who are often mentally retarded have high prevalence of class II [15,41] attributed to early eruption of primary teeth and abnormal tongue and head posture [15,[42][43][44]. Furthermore, lip incompetence and failure of the maxillary orbicularis muscle is another cause of excessive overjet in cerebral palsy patients [45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Wyniki dotyczące średniej wartości liczby D 3 MFT i jej składowych D 3 T, MT, FT, oraz liczby zębów z próchnicą, zębów usuniętych oraz zębów wypełnionych w badanej grupie pacjentów przed leczeniem w znieczuleniu ogólnym przedstawiono w tabeli 1 oraz na rycinie 1.…”
Section: Wynikiunclassified
“…Stwierdzono również, że badani z innymi chorobami (układu sercowo-naczyniowego, układu oddechowego, zwojakiem zarodkowym współczul-nym, ziarnicą złośliwą, stwardnieniem rozsianym) mieli istotnie wyższą średnią wartość liczby D 3 MFT przed leczeniem (18,6) w porównaniu z badanymi z upośledzeniem umysłowym (12,31), Tabela 2. Średnia wartość liczby D 3 MFT i jej składowych D 3 T, MT, FT w badanej grupie z uwzględnieniem płci, wieku, rozpoznania, miejsca zamieszkania, sprawowanej opieki oraz kolejności zabiegu MFT przed leczeniem była istotnie wyższa wśród pacjentów, u któ-rych wcześniej zęby leczono w znieczuleniu ogól-nym (17,07) w porównaniu z badanymi, dla któ-rych był to pierwszy zabieg (12,68) (p = 0,03).…”
Section: Wynikiunclassified
See 1 more Smart Citation
“…12 Study of dental treatment needs of 300 children (aged 9-13 years) with disabilities in Melbourne found that 41 % of them required simple treatment; including caries treatment, periodontal therapy and oral health promotion. 13 Dental anomaly is often found in Down syndrome patient. The incidence is about 73%.…”
mentioning
confidence: 99%